3. EVALUATION OF THE RESULTS OF UTERUS CONSERVATION SURGERY IN PLACENTA ACCLAIMARTORS AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL IN 2022 - 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the clinical and paraclinical characteristics of pregnant women with placenta accreta at Nghe An Obstetrics and Pediatrics Hospital and comment on the results of diagnosis and uterine preservation surgery in placenta accreta at Nghe An Obstetrics and Pediatrics Hospital in 2022 - 2023.Subjects and methods of research: Retrospective descriptive study on 33 patients who underwent one-stage uterine conservation surgery due to placenta accreta with a gestational age > 28 weeks at Nghe An Obstetrics and Pediatrics Hospital from January 2022 to December 2023.Results: Patients admitted to the hospital were mainly asymptomatic (48.5%), 93.9% underwent elective surgery, gestational age at surgery was mainly from 34 to 36 weeks and 6 days (57.5%). The preoperative diagnosis rates of Accreta, Increta and Percreta were 78.8%, 18.2% and 3%, respectively; the intraoperative diagnosis rates were 69.7%, 24.2% and 6.1%, respectively; in addition, the postoperative diagnosis rates by histopathology were 51.5%, 21.2% and 6.1%, respectively. The rate of uterine preservation was successful in 100% of cases. Intraoperative complications: Blood loss was mainly from 500 - 1500ml (60.6%), there was no ureteral injury during surgery, surgery time was mainly from 120 minutes to 180 minutes (63.6%). Postoperative complications: There was no postoperative bleeding. There were 6.1% of mild postoperative infections that were treated with internal medicine. The maternal outcome was 100% survival, healthy upon discharge. The infant outcome was 32/33 healthy babies after treatment in the Neonatal Unit.Conclusion: Through a study of 33 cases of one-stage uterine preservation surgery in RCRL with a preservation rate of 100% of cases, intraoperative and postoperative complications were very rare, and the results of 100% of healthy cases upon discharge from the hospital demonstrated that one-stage uterine preservation surgery due to placenta accreta is a method of uterine preservation with a high success rate and low complications.
Keywords: Placenta accreta; one-time uterine preservation